For a New Form of Forest Living in Future Literature - Gopaul, Sooshilla (Literary Studies, 2024)
Building on Arjun Appadurai’s scheme of the imagined world of scapes, I propose an entry into his ethnoscape to foster a new form of forest living in literature. Appadurai’s ethnoscape, just like his technoscape, can be physically present as different enterprises in different parts of the planet Earth but they all form one entity. Similarly, we may have forests in different parts of the world but they can be considered as one entity. I put forward the idea that in a new form of forest literature, we use acquired knowledge and experience but also devise new strategies. Thus, we will not repeat mistakes the Anthropocene has committed but use what it has achieved so far. In this paper, I refrain from using a messianic approach. Basing myself on the trend that 21st-century Literature is taking I suggest: first that Magic Realism be brought in; secondly, we retrieve Goddess Aranyani from the Rig Veda and the mood of experiencing the joys of expectancy from the Mullai forest found in Sangam literature; thirdly, as a new element, we weave in the principle of homeostasis in nature. As far as perspectives are concerned I recommend the cosmopolitan ones with strong undertones of the personal voice as used by the two recent Nobel Prize Winners for literature. I bring in Jojo Moyes’s novel The Giver of Stars to support my plea for a new form of the forest living in literature.